1976
DOI: 10.1177/107769907605300219
|View full text |Cite
|
Sign up to set email alerts
|

Components of Credibility of a Favorable News Source

Abstract: This department is devoted to shorter reports on research in the communications field. Readers are invited to submit summaries of investigative studies interesting for content, method or implications for further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…But diverse dimensions have emerged from factor analyses of the credibility concept (see, e.g., Markham 1968;Singletary 1976), and there does not appear to be a multidimensional stability underiying the concept. Credibility is not a trait that people ascribe consistently to a channel but, rather, a highly situational assessment (Berlo, Lemert, and Mertz 1969;Chaffee 1982).…”
Section: The Skeptical Dispositionmentioning
confidence: 98%
“…But diverse dimensions have emerged from factor analyses of the credibility concept (see, e.g., Markham 1968;Singletary 1976), and there does not appear to be a multidimensional stability underiying the concept. Credibility is not a trait that people ascribe consistently to a channel but, rather, a highly situational assessment (Berlo, Lemert, and Mertz 1969;Chaffee 1982).…”
Section: The Skeptical Dispositionmentioning
confidence: 98%
“…They found that highly experienced users may be overly skeptical and that inexperienced users tend to over-rely on suggestions from computers, as compared to a control condition with mimeographed lists of the same suggestions. This finding fits with an early belief among researchers that users are likely to be "in awe" of computers, viewing them as credible in a wide range of domains (Pancer, 1992), but later experiments show little evidence for this belief (Andrews and Gutkin, 1991;Waern and Ramberg, 1996 (Singletary, 1976) and (Vandenbergh, Soley, and Reid, 1981) asked participants in their studies to imagine a specific high-credibility source (in Singletary's case, a news person; in VandenBergh et al's, an advertiser) and to list as many terms as possible that, in the participant's view, gave credibility to that source. Other researchers either sampled the existing literature to create a list of candidate terms based upon their review or relied upon intuition.…”
Section: Contexts Affect Credibility Constructssupporting
confidence: 71%
“…Facing this patchy universe, Metzger et al (2003) concluded ''Disagreements about the relative importance of the dimensions of source credibility led to the construction of various scales to measure this concept, each reflecting the priority of dimensions identified by particular researchers'' (p. 298). However, in a comprehensive review of the existing source credibility measures, we found-fully in line with Hovland and colleaguestrustworthiness (Bowers & Phillips, 1967;Lee, 1978;Markham, 1968;Mosier & Ahlgren, 1981;Ohanian, 1990;Salwen 1987;Singletary, 1976;Tuppen, 1974;VandenBergh, Soley, & Reid, 1981;White, 1990;Whitehead, 1968) and expertise (Lee, 1978;Markham, 1968;Newel & Goldsmith, 2001;Ohanian, 1990;Salwen, 1987;Simpson & Kahler, 1980;Tuppen, 1974) to form the central components of credibility.…”
Section: Credibility Researchmentioning
confidence: 69%